Comparisons of laboratory-based methods to calculate jump height and improvements to the field-based flight-time method - Wade, L.; Lichtwark, G. A.; Farris, D. J. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Laboratory methods that are required to calculate highly precise jump heights during experimental research have never been sufficiently compared and examined. Our first aim was to compare jumping outcome measures of the same jump, using four different methods (double integration from force plate data, rigid-body modeling from motion capture data, marker-based video tracking, and a hybrid method), separately for countermovement and squat jumps. Additionally, laboratory methods are often unsuitable for field use due to equipment or time restrictions. Therefore, our second aim was to improve an additional field-based method (flight-time method), by combining this method with an anthropometrically scaled constant. Motion capture and ground reaction forces were used to calculate jump height of twenty-four participants who performed five maximal countermovement jumps and five maximal squat jumps. Within-participant mean and standard deviation of jump height, flight distance, heel-lift, and take-off velocity were compared for each of the four methods. All four methods calculated countermovement jump height with low variability and are suitable for research applications. The double integration method had significant errors in squat jump height due to integration drift, and all other methods had low variability and are therefore suitable for research applications. Rigid-body modeling was unable to determine the position of the center of mass at take-off in both jumping movements and should not be used to calculate heel-lift or flight distance. The flight-time method was greatly improved with the addition of an anthropometrically scaled heel-lift constant, enabling this method to estimate jump height and subsequently estimate power output in the field.